2017
DOI: 10.1093/neuros/nyw126
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Resource Utilization and Patient-Reported Outcomes Following Elective Surgery for Intradural Extramedullary Spinal Tumors

Abstract: BACKGROUND:Healthcare resource utilization and patient-reported outcomes (PROs) for intradural extramedullary (IDEM) spine tumors are not well reported. OBJECTIVE: To analyze the PROs, costs, and resource utilization 1 year following surgical resection of IDEM tumors. METHODS: Patients undergoing elective spine surgery for IDEM tumors and enrolled in a single-center, prospective, longitudinal registry were analyzed. Baseline and postoperative 1-year PROs were recorded. One-year spine-related direct and indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…There was no worsening in functional status. This is also consistent with the results of other studies that showed a good response and improved quality of life in patient follow-up [6][7][8][9][10] . Riad et al, for example, observed a sensory and / or motor improvement in 87% of the patients and 85% of those who presented gait changes at admission were able to walk autonomously at the end of the follow-up 6 .…”
Section: Discussionsupporting
confidence: 92%
“…There was no worsening in functional status. This is also consistent with the results of other studies that showed a good response and improved quality of life in patient follow-up [6][7][8][9][10] . Riad et al, for example, observed a sensory and / or motor improvement in 87% of the patients and 85% of those who presented gait changes at admission were able to walk autonomously at the end of the follow-up 6 .…”
Section: Discussionsupporting
confidence: 92%
“…The early recognition of signs and symptoms, that allows diagnosis of early-stage disease before spinal cord damage occurs, can reduce the risk of postoperative morbidity and may improve surgical outcome (29)(30)(31). A strong correlation has been suggested between the degree of functional impairment and the extent of damage to the spinal cord or spinal roots: the greater the impairment, the longer the persistence of the lesion, and the more difficult postoperative functional recovery will be, despite radical tumor removal (32)(33)(34)(35). In this regard, the present study confirmed previous results of the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the operation fields of these approaches are deep and narrow and require the resection of vital components of the atlantoaxial spine. The prolonged surgical time of the combined anterior-posterior approach has been linked to iatrogenic traumatism[ 4 ]. The posterior approach is the most widely used.…”
Section: Introductionmentioning
confidence: 99%